Ultrasound-assisted DLLME with natural deep eutectic solvent and smartphone-based colorimetry for Pb(II) detection in water - Nayyer Azhdari; Biuck Habibi; Zahra Ayazi; Elaheh Rahimpour (Sensing and Bio-Sensing Research)
This research presents a novel, cost-efficient and high-performance method for preconcentration and detection of lead ions [Pb(II)] using ultrasound-assisted dispersive liquid-liquid microextraction (USA-DLLME) combined with digital image colorimetry (DIC). The extraction phase included a natural deep eutectic solvent (NADES) made from choline chloride and thymol. The digital colorimetric analysis is based on the color transition of the Pb(II)[1-(2-pyridylazo)-2-naphthol (PAN)]2 complex, which changes from orange to wine red color in ethanol. The images of the NADES solution containing Pb(II) complex were captured using an Android smartphone and processed with the Color Grab application. Under the optimum conditions, a calibration curve for Pb(II) was constructed using the green channel intensity over the concentration range of 10 to 300 ng/mL, yielding a strong linear correlation (R2 = 0.9929). The detection limit and quantification limit were determined as 5.21 ng/mL and 17.38 ng/mL, respectively. The method demonstrated good precision with relative standard deviations (RSD) of 1.02 % within a single day and 1.25 % across multiple days. Finally, the current method was successfully applied to quantify the Pb(II) in mineral, tap and river water samples, achieving relative recoveries between 94.0 % and 102.5 %, confirming its reliability and suitability for analyzing real water samples.